2022
DOI: 10.21037/tau-22-280
|View full text |Cite
|
Sign up to set email alerts
|

Baseline urine pH is related to effective urine alkalization by short-term alkaline water supplementation: data from a self-controlled study in healthy Chinese volunteers following a systematic review and meta-analysis of literature

Abstract: Background: The outcomes of urine alkalization with alkaline water supplementation vary greatly across studies and therefore remain inconclusive, probably arising from differences in study design, ethnic group, and source of alkaline water, which needs further clarification. With a systematic review of literature, followed by an empirical observation among healthy Chinese volunteers, we aimed to investigate the outcomes of urine alkalization with alkaline water vs. daily drinking water, and whether these outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…Notably, some of these studies have suggested improved hydration, an increase in postexercise urine pH and increase in urine pH with high mineral alkaline water. 5,6 As a result of these studies many companies and online platforms have capitalized on marketing all forms of alkaline water (eg, commercially produced as well as true mineral water) as having the ability to raise urine pH. 7,8 To the best of our knowledge, no study has previously evaluated the potential use of commercially produced alkaline water for alkalinizing the urine pH to benefit uric acid and cystine urolithiasis.…”
mentioning
confidence: 99%
“…Notably, some of these studies have suggested improved hydration, an increase in postexercise urine pH and increase in urine pH with high mineral alkaline water. 5,6 As a result of these studies many companies and online platforms have capitalized on marketing all forms of alkaline water (eg, commercially produced as well as true mineral water) as having the ability to raise urine pH. 7,8 To the best of our knowledge, no study has previously evaluated the potential use of commercially produced alkaline water for alkalinizing the urine pH to benefit uric acid and cystine urolithiasis.…”
mentioning
confidence: 99%
“…One of these studies showed that people eating acid-content or alkaline-content diets changed the urine pH in a similar way [21]. A metaanalysis and a study of humans revealed that alkali water supplementation may be beneficial for alkalization in people with low urine pH [22]. Another study of volunteers showed that the amount of water drunk may convert to alkaline urine at higher proportions in men compared to women [18].…”
Section: Discussionmentioning
confidence: 99%
“…The color intensity is proportional to the pH of the sample. This color is then matched to a standard color scheme to determine the pH [17]. In our study, the color comparator method was used for pH measurements.…”
Section: Methodsmentioning
confidence: 99%